Health aid and health improvement in sub-saharan africa: accounting for the heterogeneity between stable states and post-conflict states - (:unkn) unknown (My University, 2014)
Using a sample of 34 sub-Saharan African countries over the period 1990–2012, thispaper reveals that health aid helps to improve health outcomes in sub-Saharan African countries.More specifically, for each additional unit of health aid, the prevalence of HIV decreases by 8.3%and child mortality decreases by 64% over 4 years. This effect operates mainly through theimprovement of female education and the increase in health spending. Furthermore, the results donot support the hypothesis of a significant difference between post-conflict states and stable statesin terms of aid effectiveness.
Keywords: African Research